Problems in Mastering English: An Analysis from Students’ Perspective - Nofrina Eka Putri (English Education Study Program Faculty of Teacher Training and Education, 2019)
This research is intended to reveal the problems faced by students in mastering English. This research is categorized into a quantitative study. The sample of this research was 75 students taking MKU Bahasa Inggris (English for General Purposes) class in the second semester of Academic Year 2018/2019. The data were obtained by using the questionnaire, and they then were analyzed quantitatively. The findings showed that to master English, the students get problems related to the limited stock of vocabulary, inability to construct sentences, inability to provide appropriate responses, and lack of opportunities to practice English beyond the class. Based on the findings, it is concluded that the students’ less competence in using English has resulted from their basic English capability and environmental supports.